Case report: Rare case of multinodular and vacuolar neuronal tumors in the cerebellum - Wang, Zhou; Ma, Jiwei (Frontiers in Neurology, 2024)
Multinodular and vacuolar neuronal tumor (MVNT) is a rare and benign neuroepithelial tumor. Most reports describe tumors located in the cerebral hemisphere. A literature review found that 15 cases were located in the posterior cranial fossa, but all lacked pathological evidence. In this case, a patient sought medical attention due to insomnia and irritability. Neuroepithelial tumors were found in the imaging, and the patient underwent radiation therapy. Three years later, malignant tumors were found upon imaging examination. After surgical resection and pathological testing, MVNT occurring in the cerebellum was diagnosed. MVNT is rare in the cerebellum, and direct imaging diagnosis becomes difficult after treatment. Therefore, our report of this case helps to further accurate understanding of the imaging, pathological, and molecular genetic changes occurring before and after MVNT treatment, and will improve the accuracy of pre-treatment diagnosis and reduce the likelihood of overtreatment.